Magnitude and predictors of first-line antiretroviral therapy regimen change among HIV infected adults: A retrospective cross sectional study. (September 2022) - Alema, Niguse Meles; Asgedom, Solomon Weldegebreal; Maru, Mahlet; Berihun, Beletu; Gebrehiwet, Teklu; Atey, Tesfay Mehari; Demsie, Desalegn Getnet; Bantie, Abere Tilahun; yehualaw, Adane; Taferre, Chernet; Seid, Sofia Assen; Girma, Timsel; et al.
Abstract: Background: Regimen change remains a significant challenge towards the achievement of human immunodeficiency virus (HIV) treatment success. In developing countries where limited treatment options are available, strategies are required to ensure the sustainability and durability of the starting regimens. Nevertheless, information regarding the rate and predictors of regimen change is limited in these settings. Objective: This study was undertaken to determine the prevalence and predictors of changes in ART regimens among patients initiating highly active antiretroviral therapy (HAART) at XX. Materials and methods: An institutional based retrospective cross-sectional study was conducted among adult naïve HIV patients who had initiated HAART at XX between 2010. Data were extracted by reviewing their medical charts using a pretested structured check-list. The Kaplan–Meier survival analyses were used to describe the probability of ARV regimen changes while Cox proportional hazard regression models were employed to identify the predictors of ARV regimen modifications. Data were analyzed using SPSS version 21 software, and statistical significant was deemed at p < 0.05. Results: A total of 770 patients were enrolled in this study of these 165 (21.43%) had their ART regimen modified at least once. Drug toxicity was the main reason for regimen change followed by TB comorbidity, and treatment failure. Positive baseline TB symptoms (aHR = 1.63, p = 0.037), and Zidovudine based regimen (aHR = 1.76, p = 0.011) as compared to Stavudine based regimen were at higher risk of ART modification. Conversely, urban residence, baseline World Health organization (WHO) stage 2 as compared to WHO stage 1, baseline CD4 count ≥301 as compared to CD4 count ≤200 were at lower risk of ART modification. Conclusion: The rate of initial HAART regimen change was found to be high. Thus, less toxic and better tolerated HIV treatment options should be available and used more frequently. Moreover, early detection and initiation of ART by the government is highly demanded to maximize the benefit and reduce risk of ART modifications. Highlights: The majorities (57.4%) of the patients were female and the mean age of the study participants was 32.9 ± 9.5 A total of 165 (21.4%) participants experienced antiretroviral regimen changes within two years of follow-up period. The highest rate of treatment modification was found among patients receiving fixed-dose combination of AZT+3 TC + NVP 81 (49.0%). Drug toxicity was the main reason for ARV regimen change, which accounts for 74 (41.3%) of regimen change. Anemia was the main forms of toxicities which accounted for 45(36.3%).